Sustainability of entrepreneurial journalistic arrangements in Brazil: a study of seven digital-native ones - Silveira, Stefanie Carlan da; Costa Ramos, Alessandra Natasha (Brazilian journalism research, 2022)
ABSTRACT – This article investigates how journalistic arrangements that define themselves as entrepreneurs work on the elements of value proposition, sources of revenue and customer relationships in their business models and how much this reflects on their financial sustainability. As a method of this qualitative-quantitative exploratory research, the initiatives present in the Map of Independent Journalism, by Agência Pública, were categorized into active and closed/inactive. Within the active ones, a screening was carried out to verify which of these were in fact journalistic. For data collection, a questionnaire was applied, with a set of questions organized from the theoretical framework proposed by Osterwalder and Pigneur (2011); Skaggs and Youngt (2003); Amit and Zott (2001); Benvenido (2018); Figaro (2018). As a result, there was a direct relationship between sustainability and dedication of professionals to the profitability of the project and the relationship with the public. In addition, all respondents answered that they invest in efficiency and innovation strategies to create value for the audience. RESUMO – Investiga-se como arranjos jornalísticos que se autodefinem empreendedores trabalham os elementos proposta de valor, fontes de receita e relacionamento com clientes em seus modelos de negócio e o quanto isso reflete em sua sustentabilidade financeira. Como método desta pesquisa quali-quantitativa de natureza exploratória, categorizou-se em ativas e encerradas/inativas as iniciativas presentes no Mapa do Jornalismo Independente, da Agência Pública. Dentro das ativas, realizou-se triagem para verificar quais destas eram de fato jornalísticas. Para coleta de dados, foi aplicado questionário, com conjunto de perguntas organizado a partir do referencial teórico proposto por Osterwalder e Pigneur (2011); Skaggs e Youndt (2003); Amit e Zott (2001); Benvenido (2018); Figaro (2018). Como resultados, percebeu-se relação direta entre sustentabilidade e dedicação dos profissionais à rentabilização do projeto e ao relacionamento com o público. Além disso, todos os investigados responderam que investem em estratégias de eficiência e inovação para criação de valor junto à audiência. RESUMEN – Investiga cómo los proyectos periodísticos que se definen a sí mismos como emprendedores trabajan sobre los elementos de la propuesta de valor, las fuentes de ingresos y las relaciones con los clientes en sus modelos de negocio y cuánto se refleja esto en su sostenibilidad financiera. Como método de esta investigación exploratoria cualitativa-cuantitativa, las iniciativas presentes en el Mapa del Periodismo Independiente, de Agência Pública, fueron categorizadas en activas y cerradas/inactivas. Dentro de los activos, se realizó un tamizaje para verificar cuáles de estos eran en realidad periodísticos. Para la recolección de datos se aplicó un cuestionario, con un conjunto de preguntas organizadas a partir del marco teórico propuesto por Osterwalder y Pigneur (2011); Skaggs y Youngt (2003); Amit y Zott (2001); Benvenido (2018); Fígaro (2018). Como resultado, hubo una relación directa entre la sostenibilidad y la dedicación de los profesionales a la rentabilidad del proyecto y la relación con el público. Además, todos los encuestados respondieron que invierten en estrategias de eficiencia e innovación para crear valor para la audiencia.